2007
DOI: 10.1097/dad.0b013e318159b45e
|View full text |Cite
|
Sign up to set email alerts
|

Large-cell Neuroendocrine Carcinoma of the Skin, With Lymphoid Stroma

Abstract: We report two cases of a large-cell neuroendocrine carcinoma of the skin as a distinct histological category. The patients are a 63-year-old woman with a 7-mm reddish round nodule on her nose for 4 months, and a 95-year-old man with several hemorrhagic nodules on the external ear for 28 months. The first patient had two positive sentinel lymph nodes. The tumors from both patients consisted of islands of pleomorphic large cells within a lymphoid stroma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Two other similar cases of an MCC with a follicular lymphocytic infiltrate were recently described [4]. Kasami et al [11] have reported a new entity that they called large cell neuroendocrine carcinoma of the skin; the two cases they described showed an abundant lymphocytic infiltration making the differential diagnosis difficult with MCC mimicking LEL carcinoma and especially an LEL carcinoma of the skin. In this proposed new entity, tumor cells are larger and more pleomorphic than those of conventional MCC, and the characteristic perinuclear immunostaining with cytokeratin 20 is not found.…”
Section: Discussionmentioning
confidence: 97%
“…Two other similar cases of an MCC with a follicular lymphocytic infiltrate were recently described [4]. Kasami et al [11] have reported a new entity that they called large cell neuroendocrine carcinoma of the skin; the two cases they described showed an abundant lymphocytic infiltration making the differential diagnosis difficult with MCC mimicking LEL carcinoma and especially an LEL carcinoma of the skin. In this proposed new entity, tumor cells are larger and more pleomorphic than those of conventional MCC, and the characteristic perinuclear immunostaining with cytokeratin 20 is not found.…”
Section: Discussionmentioning
confidence: 97%
“…Another entry to the group came in the form of EMPSGC, first described in 1997 and later found to be the likely precursor of mucinous carcinoma of the skin . The most recently described and least recognized subset of primary cutaneous neuroendocrine tumors, and the focus of this communication, is that of LCNCS …”
Section: Discussionmentioning
confidence: 99%
“…Up to now, the majority of case reports concerning cNEC of the external ear are diagnosed as MCC, which possesses similar clinical, pathological, and immunohistochemical characteristics to small cell neuroendocrine carcinoma. However, cases of both cutaneous endocrine adenoma [3] and large cell cNEC [5] occurring in external ear have also been reported, which indicates that MCC is not the only type of neuroendocrine tumor of the external ear. Also, considerable debates on the proper name of this tumor still exist because no concrete evidence has been found to prove whether cNEC is derived from epidermal Merkel cells, dermal neuroendocrine cells, or pluripotent dermal stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…Much less often, cNEC is diagnosed in the external ear. To our best knowledge, only 23 cases of cNEC of the external ear have been reported [25], and only 3 of them were found in the external auditory canal [6, 7]. …”
Section: Introductionmentioning
confidence: 99%